Description of a new species of Dascillus Latreille from Sichuan, China Coleoptera: Dascillidae) - Jin, Zhenyu; Xie, Guanglin; Yang, Qixin (Zootaxa, 2016)
Dascillidae are a small and rarely studied family that includes nine currently recognized genera (Lawrence 2005; Ivie & Barclay 2011; Jin et al. 2013) and about 80 described species divided into two poorly defined subfamilies—a free-living Dascillinae and variously morphologically modified Karumiinae, some of which are apparently associated with subterranean termites. Dascillinae inhabit mostly forested areas of the Northern Hemisphere and Australia (Lawrence 2005).